2010
DOI: 10.1007/s11356-009-0285-3
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of chemical effects on aromatase activity using the H295R cell line

Abstract: For future work with the H295R, it is recommended that a combination of direct and indirect aromatase measurements is used because it was best in predicting the effects of a chemical on E2 production and its mechanism of action. Further, it was shown that direct AA measurements, which are a common way to measure AA, must be used with caution in vitro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
26
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(30 citation statements)
references
References 36 publications
2
26
0
2
Order By: Relevance
“…For example, simultaneously examination of chemical-induced effects at transcriptional, enzymatic, and metabolite levels in the H295R cells has been used to characterize the disruption of steroid hormone production by endocrine active chemicals [30,31,33]. A recent study demonstrated that the strategy of measuring multiple endpoints is effective to differentiate between chemical-caused direct inhibition of aromatase activity from indirect inhibition (e.g., by altering transcriptional expression) [47].…”
Section: Applicationmentioning
confidence: 99%
“…For example, simultaneously examination of chemical-induced effects at transcriptional, enzymatic, and metabolite levels in the H295R cells has been used to characterize the disruption of steroid hormone production by endocrine active chemicals [30,31,33]. A recent study demonstrated that the strategy of measuring multiple endpoints is effective to differentiate between chemical-caused direct inhibition of aromatase activity from indirect inhibition (e.g., by altering transcriptional expression) [47].…”
Section: Applicationmentioning
confidence: 99%
“…In addition, the H295R model can be used to measure the effects of EDCs on the activity of enzymes involved in hormone production {e.g., Aromatase/CYP19 activity [22] or CYP17 activity [76]}. Moreover, the model can be exploited for proteome studies following EDC exposure [77,78].…”
Section: Endocrine Disruption At Hormone-production Levelmentioning
confidence: 99%
“…Recent advances in cell biology and biotechnology have allowed development of a new generation of bioassays focused on hormonal nuclear receptor signaling [14][15][16][17][18] and steroidogenesis pathways [11,[19][20][21][22][23][24][25]. Some of these new bioassays are based on the ability to introduce specific properties and reporter genes into stable cellular systems.…”
Section: Introductionmentioning
confidence: 99%
“…Les changements enregistrés par le système d'essai sous la forme d'une altération de la production de T et d'E2 peuvent être le résultat d'une multitude d'interactions différentes des substances d'essai avec les fonctions stéroïdogéniques exprimées par les cellules H295R. Cela inclut la modulation de l'expression, de la synthèse ou de la fonction des enzymes intervenant dans la production, la transformation ou l'élimination des hormones stéroïdes (12) (13) (14). L'inhibition de la production d'hormones peut être due à une liaison compétitive directe avec une enzyme dans la voie de synthèse, à l'impact sur des cofacteurs comme la NADPH (Nicotinamide adénine dinucléotide phosphate) et l'AMPc (Adénosine monophosphate cyclique), et/ou à l'augmentation du métabolisme des stéroïdes ou la suppression de l'expression génique de certaines enzymes dans la voie de la stéroïdogenèse.…”
unclassified